2022
DOI: 10.1186/s13104-022-05977-6
|View full text |Cite
|
Sign up to set email alerts
|

Catastrophic health expenditure due to hospitalisation for COVID-19 treatment in India: findings from a primary survey

Abstract: Objective The COVID-19 pandemic has caused widespread illness and a significant proportion of the infected required hospitalisation for treatment. People in developing countries like India were vulnerable to high hospitalisation costs. Despite its crucial importance, few primary studies are available on this aspect of the pandemic. This study was aimed at finding out the out of pocket expenditure (OOPE) and incidence of catastrophic expenditure on hospitalisation of persons infected with COVID-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
27
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(36 citation statements)
references
References 34 publications
5
27
0
Order By: Relevance
“…[33] As documented in east-central India, those hospitalised in public hospitals [3.2% (1.8-5.7%)] incurred CHE more than those hospitalized in private hospitals [58.9% (50.5-66.74%)]. Overall, 20.3% (16.9-24.1%) of those hospitalised had CHE, [25] which is more comparable with our study ndings. Comorbidities and being elderly were associated with the severity of COVID-19 and the need for hospitalisation.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…[33] As documented in east-central India, those hospitalised in public hospitals [3.2% (1.8-5.7%)] incurred CHE more than those hospitalized in private hospitals [58.9% (50.5-66.74%)]. Overall, 20.3% (16.9-24.1%) of those hospitalised had CHE, [25] which is more comparable with our study ndings. Comorbidities and being elderly were associated with the severity of COVID-19 and the need for hospitalisation.…”
Section: Discussionsupporting
confidence: 88%
“…[25] Our analysis found that households that received insurance co-payments/reimbursement were six times more likely to experience CHE, pointing towards likely ineffectiveness of insurance copayment/reimbursement, whether public or private. Similar ndings from India [25] and other countries such as Peru and USA have reported high OOPE for COVID-19 hospitalization and the ineffectiveness of health insurance. [16, 39,40] Tamil Nadu State reports that approximately 66.5% of households are covered by the Chief Minister's Comprehensive Health Insurance Scheme (CMCHIS), implemented to provide nancial protection to the vulnerable, compared to a national average of 41% of households.…”
Section: Discussionsupporting
confidence: 59%
See 1 more Smart Citation
“…This monthly income showed a decrease to INR 25,000 (USD 337. [24]. Another study on COVID-19 patients from Western India revealed that even after the government scheme, the median difference in the final bill and the amount reimbursed through government schemes was INR 59,560 ($ 807.75) [25].…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the designated four roles described earlier, Mitanins were expected to carry out a number of tasks related to the COVID-19 pandemic including promoting behavioural change, door to door visits for surveillance of relevant symptoms and monitoring the cases under home isolation. The data collection was done in November 2020 and the first wave of the pandemic was in progress in Chhattisgarh in that period [ 26 ]. The sixth and the last purpose of time use was for data collection, routine reporting about their work and other paper work of administrative nature.…”
Section: Methodsmentioning
confidence: 99%